2021
DOI: 10.1007/s11033-021-06637-x
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic effect of myricetin and apigenin against lipopolysaccharide-induced acute liver injury

Abstract: Background Liver has an important role in the initiation and progression of multiple organ failure that occurs in sepsis. Many natural active substances can be used to reduce the liver injury caused by sepsis. For this aim, the effects of myricetin and apigenin on mice model of acute liver injury was evaluated in this study. Methods and resultsThirty-six mice were randomly divided into six groups as; control, lipopolysaccharide (LPS) (5 mg/kg), LPS + myricetin (100 mg/kg), LPS + myricetin (200 mg/kg), LPS + ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 53 publications
0
18
0
Order By: Relevance
“…MEBr increased the activity of the antioxidant enzymes SOD and CAT. It has been shown that components present in MEBr such as quercetin, myricetin, kaempferol, and p-coumaroyl increase the activity of the antioxidant enzymes SOD and CAT [38][39][40][41][42][43]. SOD is responsible for dismuting the radical superoxide anion (O2 •-) to H 2 O 2 , which is neutralized by CAT, limiting the production of hydroxyl radicals ( • OH) [44].…”
Section: Discussionmentioning
confidence: 99%
“…MEBr increased the activity of the antioxidant enzymes SOD and CAT. It has been shown that components present in MEBr such as quercetin, myricetin, kaempferol, and p-coumaroyl increase the activity of the antioxidant enzymes SOD and CAT [38][39][40][41][42][43]. SOD is responsible for dismuting the radical superoxide anion (O2 •-) to H 2 O 2 , which is neutralized by CAT, limiting the production of hydroxyl radicals ( • OH) [44].…”
Section: Discussionmentioning
confidence: 99%
“…On days 21-25 after the beginning of the sensitization period, mice were sensitized by instillation of OVA solution into the bilateral nasal cavities by using a micropipette (100 μg/mice) once a day. Apigenin (100 μl/mice) at doses of 50, 100 or 200 mg/kg body weight 22,23 or dexamethasone (100 μl/mice) at a dose of 5 mg/kg body weight were orally administered to OVA-sensitized animals once daily from days 15 to 20. Mice in control group were given saline alone on the same schedule.…”
Section: Ova-induced Allergic Mouse Modelmentioning
confidence: 99%
“…Apigenin ( 1 ) and plantamajoside ( 25 ) can reduce pro-inflammation mediators (TNF-α, IL-1β, IL-6, IL-17A, NO, PGE2, iNOS, COX-2, NLRP3, and NF-κB); improve anti-inflammation cytokines (TGF-β and IL-10); and restrain the phosphorylation of NF-κB, IκB, and IKK proteins to inhibit inflammatory responses. , Similarly, luteolin ( 2 ), acteoside ( 27 ), and isoacteoside ( 28 ) regulate the expression of factors in the anti-inflammatory function, including (I) inflammatory mediators COX-2, iNOS, PGE2, NO, TLR4, Myd88, ICAM-1, and VCAM-1; (II) pro-inflammatory cytokines (like TNF-α, NLRP3, IL-1β, IL-17, and IL-18); (III) anti-inflammatory factors [such as arginase 1 (Arg-1), TGF-β, IL-4, IL-6, IL-10, and NO synthase-2]; and (IV) chemoattractant cytokines, such as C–C motif chemokine ligands (CCL)-2 and CCL-3 and the CXC motif chemokine ligands (CXCL)-1, CXCL-2, and CXCL-10. , It is reported that polysaccharides inhibit the secretion of TNF-α, IL-6, IL-10, IL-2, and IL-1β induced by LPS to prevent liver injury …”
Section: Biological Activities and Molecular Pharmacologymentioning
confidence: 99%
“…Studies have shown that apigenin ( 1 ) administration blocks the secretion of pro-inflammatory cytokines and the activation of NF-κB; downregulates the expression of NLRP-3, TLR4, TNF-α, AMPK, and NF-κB; , and decreases the transcriptional activity of NF-κB and the phosphorylation of NF-κB, IκB, IKK, Lyn, Syk, MAPK, ERK, and JNK. , Similarly, luteolin ( 2 ) exerts an anti-inflammatory effect by downregulating the TLR4-mediated NF-κB/NLRP-3 and NF-κB phosphorylation. , The protective effects of acteoside ( 27 ) and isoacteoside ( 28 ) are mediated by phosphorylation of IKK, IκBα, NF-κB, and MAPK and the inactivation of TLR4-mediated NF-κB to modulate inflammation. , , Additionally, acteoside ( 27 ) restrains the inflammatory responses (TNF-α, IFN-γ, IL-6, and IL-12) by suppressing the JAK/STAT signaling pathway . Furthermore, plantamajoside ( 25 ) has anti-inflammatory properties via inhibition of the phosphorylation of IκBα, JNK, and MAPK, as well as nuclear translocation of NF-κB. , Unexpectedly, on the basis of the MAPK and NF-κB pathway, polysaccharides induce expression of MHC-II and CD86 to promote maturation of dendritic cells (DCs) and then accelerate the secretion of TNF-α and IL-12p70 so it may promote inflammatory effects .…”
Section: Biological Activities and Molecular Pharmacologymentioning
confidence: 99%
See 1 more Smart Citation